Croatian Society of Clinical Embryologists - guidelines on the epidemiological framework for the implementation of medically assisted reproduction (MAR) procedures during the COVID-19 pandemic regarding the safety of patients and medical health workers - Vujisić-Živković, Sanja (Array, 2020)
Due to the high virulence of the SARS-CoV-2 virus, the infection rate in the community has led to a state of pandemic, leading to the introduction of new emergency measures all over the world. With the aim of controlling and preventing the SARS-CoV-2 viral epidemic, the health institutions performing medically assisted reproduction (MAR) suspended any new MAR treatments in order to reduce the burden on the health care system and implement current social distancing recommendations. Considering the favorable epidemiological situation in Croatia, our perspective is that it is time to conceive, plan and bring forth guidelines for restarting work in MAR centres, taking into account the selection of patients and organization of good laboratory and clinical practices with emphasis on the safety of patients and health workers. In regard to epidemiological knowledge, it is important to establish the reorganization of work in MAR centres including epidemiological measures of reducing unnecessary stays in closed spaces, the usage of protective gear by patients and health workers and disinfection of the working spaces and equipment.